Spectroscopic reflectometry as in‐operando method for thickness determination of anodic oxide films on titanium. (21st March 2013) - Schneider, M.; Langklotz, U.; Michaelis, A.
Abstract : The present work focuses on the development of an in‐operando technique based on the visible spectroscopic reflectometry (VSR) for simultaneous determination of the oxide film formation during anodizing. The establishment of the VSR as in‐operando technique requires an extensive validation by comparative in‐situ but non‐operando thickness measurements under aqueous conditions. The investigations were carried out on anodic oxide films on pure titanium. The authors demonstrate the VSR as a simple and robust method for measurement under electrolyte covering. Additionally, an empirical correction algorithm extends the limitation of the visible reflectometry in thin film thickness. Reliable film thickness values can be measured down to ≥5 nm. The in‐operando mode yields additional information about the film growth time resolved. Copyright © 2013 John Wiley & Sons, Ltd.